Cookies Daun Kelor sebagai Inovasi Makanan Pendukung Percepatan Penurunan Stunting - Dessy Hermawan; Diah Astika Winahyu; Devi Kurniasari; Erna Listyaningsih; Prima Dian Furqoni; Karlina Herawati; Meisya Royani; Aprilia Dwi Sukowati; Wulan Anggarini; Siti Selvia Vebriani; Auliya Warda Ningrum; Arfina Yulistiani (Malahayati Nursing Journal, 2023)
ABSTRACT Indonesia is one of the countries with the highest prevalence of stunting. Stunting can be caused by a lack of food intake with nutritional value. Cookies are a type of snack that is popular and has nutritional value. This research aims to determine the effect of adding Moringa leaves on the sensory properties and protein content of Moringa leaf cookies. So Moringa leaf cookies can be used as food to support the acceleration of stunting reduction. The method used in this research is a sensory test method for cookies made with the addition of Moringa leaves. Then the most preferred cookies were tested for nutritional content in the form of protein using qualitative and quantitative tests. Based on the results of sensory tests in the form of color, aroma, texture and taste, F2 Cookies with the addition of 15 grams of Moringa leaves obtained the most favorable results. The protein content test results show that cookies contain protein with an average level of 10.622%. Cookie products meet the SNI requirements for cookie protein content. So it is hoped that Moringa leaf cake can be used as a food to support the acceleration of stunting reduction. Keywords : Stunting, Cookies, Moringa Leaves, Sensoris, Protein  ABSTRAK Indonesia merupakan salah satu negara dengan prevelensi angka stunting terbesar. Stunting bisa disebabkan karena kurangnya asupan makanan yang bernilai gizi. Cookies merupakan salah satu jenis makanan ringan yang digemari dan bernilai gizi. Penelitian ini bertujuan untuk untuk mengetahui pengaruh penambahan daun kelor terhadap sifat sensoris dan kadar protein pada cookies daun kelor. Sehingga cookies daun kelor dapat digunakan sebagai makanan pendukung percepatan penurunan stunting. Metode yang digunakan dalam penelitian ini yaitu metode uji sensoris terhadap cookies yang dibuat dengan penambahan daun kelor. Kemudian cookies yang paling disukai dilakukan uji kandungan gizi berupa protein dengan uji kualitatif dan kuantitatif. Berdasarkan hasil uji sensoris berupa warna, aroma, tekstur dan rasa, Cookies F2 dengan penambahan 15 gram daun kelor mendapatkan hasil yang paling disukai. Hasil uji kandungan protein menunjukkan cookies mengandung protein dengan kadar rata-rata 10,622%. Produk cookies memenuhi syarat SNI untuk kandungan protein cookies. Sehingga diharapkan cookies daun kelor dapat dijadikan sebagai makanan pendukung percepatan penurunan stunting. Kata Kunci: Stunting, Cookies, Daun Kelor, Sensoris, Protein